A preliminary study on the traits of Chamelea gallina (Linnaeus, 1758) in the Gulf of Antalya, Mediterranean Coast of Turkey (Levantine Sea) - TanrÄ±verdi, Raziye; Gökoğlu, Mehmet; Korun, Jale (Universitas Malikussaleh, 2019)
This study aimed to examine on some properties and to draw attention to why it cannot create an intensive stock amount of Chamelea gallina (Linnaeus, 1758) in the Gulf of Antalya in the Mediterranean coast of Turkey, Levantine Sea. Specimens of C. gallina displayed total shell legths of 6 to 32 mm, mean 14.5 mm and total weights of 0.1 to 11.44 g, mean 1.82 g. The total shell length and total weight relationship of C. gallina was calculated as TW =0.3333 * TSL 2.9894 (R² =0.9850). The mean meat yield was found as 12.10±0.9264%. A small number of C. gallina samples were collected. The majority of the collected striped venus were determined as empty shell. It was observed that the razorfish (Xyrichtys novacula) were fed with C. gallina during research. Finally, these results may draw attention the reasons why this species cannot form an intensive stock amount. It is thought that the empty shells of the striped venus can be caused from feeding of the razorfish (X. novacula) with C. gallina and environmental factor changes.Keywords: Chamelea gallina; length; weight; meat yield; mediterranean